2019
DOI: 10.1063/1.5099269
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical phenotyping of cells via impedance spectroscopy in parallel cyclic deformability channels

Abstract: This paper describes a new microfluidic biosensor with capabilities of studying single cell biophysical properties. The chip contains four parallel sensing channels, where each channel includes two constriction regions separated by a relaxation region. All channels share a pair of electrodes to record the electrical impedance. Single cell impedance magnitudes and phases at different frequencies were obtained. The deformation and transition time information of cells passing through two sequential constriction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Even if a narrow channel would obviate the need for focusing, a smaller channel section would increase the risk of clogging as well as the pressure drop. Although microfluidic devices with constriction channels have been developed 85,86 , their ability to handle a large range of different sized particles remains limited compared to classical microfluidic devices. To cope with the positional dependence without the associated risk of clogging the channel, other methods have been developed.…”
Section: Methods To Overcome the Positional Dependence In Cell/particmentioning
confidence: 99%
“…Even if a narrow channel would obviate the need for focusing, a smaller channel section would increase the risk of clogging as well as the pressure drop. Although microfluidic devices with constriction channels have been developed 85,86 , their ability to handle a large range of different sized particles remains limited compared to classical microfluidic devices. To cope with the positional dependence without the associated risk of clogging the channel, other methods have been developed.…”
Section: Methods To Overcome the Positional Dependence In Cell/particmentioning
confidence: 99%
“…Recent IFC devices applied in single-cell analysis are summarized in Table 1 . These applications, discussed in this subsection, are simply classified according to cell species, including blood cells [ 110 , 111 , 112 , 113 , 114 ], tumor cells [ 43 , 52 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ], stem cells [ 123 , 124 , 125 , 126 , 127 ], plant cells [ 60 , 128 , 129 , 130 , 131 , 132 ] and microbes [ 53 , 62 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. In terms of blood cells, researchers focused on the identification and counting of normal or diseased blood cells.…”
Section: Applications Of Single-cell Impedance Sensing Technologymentioning
confidence: 99%
“…In terms of blood cells, researchers focused on the identification and counting of normal or diseased blood cells. Studies showed the capability of IFC devices in recognition of different types of dissociated tumor cells (DTCs) [ 43 , 118 , 120 , 121 ] or circulating tumor cells (CTCs) [ 52 , 115 , 119 , 122 ]. As for stem cells, the main focus is the impedance measurement of their long-term differentiation process.…”
Section: Applications Of Single-cell Impedance Sensing Technologymentioning
confidence: 99%
See 2 more Smart Citations